2008
DOI: 10.1007/s00216-008-1835-0
|View full text |Cite
|
Sign up to set email alerts
|

Intensified biochip system using chemiluminescence for the detection of Bacillus globigii spores

Abstract: This paper reports the first intensified biochip system for chemiluminescence detection and the feasibility of using this system for the analysis of biological warfare agents is demonstrated. An enzyme-linked immunosorbent assay targeting Bacillus globigii spores, a surrogate species for Bacillus anthracis, using a chemiluminescent alkaline phosphatase substrate is combined with a compact intensified biochip detection system. The enzymatic amplification was found to be an attractive method for detection of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Goddes and coworkers introduced low-powered microwaves for triggering metal-enhanced chemiluminescence [44], and developed a probing system of protein with a detection limit of 150 fmol in less than 1 min using this technique [45]. Vo-Dinh and coworkers proposed a biochip system composed of an intensifier for signal amplification and an integrated circuit photosensing array for the detection of Bacillus globigii spores [46]. The enzymatic amplification was also used for detecting low concentrations of the spores with the intensified biochip device.…”
Section: Chemiluminescent Labelingmentioning
confidence: 99%
“…Goddes and coworkers introduced low-powered microwaves for triggering metal-enhanced chemiluminescence [44], and developed a probing system of protein with a detection limit of 150 fmol in less than 1 min using this technique [45]. Vo-Dinh and coworkers proposed a biochip system composed of an intensifier for signal amplification and an integrated circuit photosensing array for the detection of Bacillus globigii spores [46]. The enzymatic amplification was also used for detecting low concentrations of the spores with the intensified biochip device.…”
Section: Chemiluminescent Labelingmentioning
confidence: 99%
“…With the MT-MEC approach, 150 fmol of target protein could be detected in less than 1 min. Stratis-Cullum et al 45 reported an intensified biochip system for the detection of Bacillus globigii spores. The biochip detection system consisted of an intensifier and an integrated circuit-photosensing array chip.…”
Section: ·4 Enzyme-based CL Techniques 2·4·1 Hrpmentioning
confidence: 99%
“…Many applications rely on biological recognition as a means of achieving specificity for a particular target species (1)(2)(3)(4)(5). Although antibodies are most commonly employed, aptamers are another class of affinity probe and they possess a number of advantages over traditional bioreceptors (4,(6)(7)(8)(9).…”
Section: Inroductionmentioning
confidence: 99%